Sensitivity of Fiscal Balances to Oil Price Shocks: Short and Long Term Effects in the Context of Oman - Ibrahim, Omer Ali; Devesh, Sonal; Hassan, Hisham Mohamed (International Journal of Energy Economics and Policy, 2019)
This paper examines the fiscal balances in Oman and their sensitivity to oil price shocks in the short and long term, using annual data for the period 1980–2016, and employing the vector auto regression model. Results of the study indicated that oil prices Granger cause gross domestic product (GDP) growth, capital formation and inflation. Impulse response analysis showed that an innovation in the oil prices and consequent oil revenues have a similar effect on most of the macroeconomic variables in Oman. Most of these variables show an increase in the first four quarters except for government expenditure and inflation. However, in many cases, this increase has quickly shifted to decrease over the successive quarters except for inflation, which showed a steady increase over time. Variance decomposition analysis, on the other hand, indicated that net oil price shock appears to be a key factor contributing to the volatility of GDP growth over time in Oman. Keywords: Fiscal Balances, Oil Price Shocks, Oman JEL Classification: H30, C320, Q430, O503 DOI: https://doi.org/10.32479/ijeep.7351